Disorder-Enabled Pure Chirality in Bilayer Plasmonic Metasurfaces - Fasold, Stefan; Linss, Sebastian; Kawde, Trideep; Falkner, Matthias; Decker, Manuel; Pertsch, Thomas; Staude, Isabelle (ACS Photonics, 2018)
We experimentally study the effect of rotational disorder at the unit-cell level on the optical response of chiral bilayer plasmonic metasurfaces consisting of asymmetric dimers of gold nanoantennas. The structures are fabricated based on a two-step electron-beam lithography process in combination with a precision alignment procedure. For a comprehensive characterization of the chiral optical response of the fabricated bilayer metasurfaces, we combine two different measurement strategies, namely, direct measurement of the circular transmission using circularly polarized incident light and measurement of the Jones matrix using interferometric spectroscopy with linearly polarized incident light. This allows us both to do a comprehensive analysis of the polarization dependent properties and to retrieve the effective polarization eigenstates of the metasurface in the ordered and disordered regime directly from experimental data. Our results demonstrate that rotational disorder provides a route toward chiral plasmonic metasurfaces with orthogonal, purely circular eigenstates, leading to circular dichroism and optical activity without linear birefringence. Our experimental findings are additionally complemented and verified by numerical simulations for the ordered case.
CRIS-Team Scopus Importer:2023-04-20
Keywords: chirality; disorder; photonic metasurface; plasmonic